INFLUENCE OF SOCIODEMOGRAPHIC FACTORS AND BODY MASS INDEX ON DEVELOPMENT OF DEPRESSION IN OBESE AND OVERWEIGHT PEOPLE - Jandrić-Kočić, Marijana C (Medicinski časopis, 2021)
Introduction: Overweight and obesity are accompanied by changes in a person’s pathophysiology, somatic and aesthetic aspects, and often a strong unpleasant emotional component that results in the development of psychiatric disorders, primarily depression. Objective:The study aimed to examine the existence of a statistically significant association of sociodemographic factors and body mass index (BMI) with the intensity of depression in obese and overweight people. Method: The study was performed as a cross-sectional study at the Health Center Krupa na Uni (Republika Srpska, Bosnia and Herzegovina) in the period from 01.12.2018. to 01.10.2019. The sample consisted of 90 overweight and obese individuals, 58 (64.4%) women and 32 (35.6%) men with a mean age of 55.0 ± 6.9 years. In addition to the general questionnaire, the study used Beck’s Depression Inventory (BDI). The chi-square test was used in the statistical analysis of the data. Result: Depression was found in 45 (50.0%) study participants (31.1% mild depression, 15.6% moderate depression, and 3.3% severe depression). There was a statistically significant higher intensity of depression in female subjects and body mass index ≥ 25. Conclusion: Female gender is an independent predictor of depression intensity in overweight and obese individuals. There is a strong correlation between body mass index and depression intensity. Level of education, place of residence and age are not consistent with the presence and severity of depression in overweight and obese individuals.